The AI Military Race : common good governance in the age of artificial intelligence - Garcia, Denise (Oxford, United Kingdom: Oxford University Press, 2023)
The AI Military Race examines the complexities entailed in creating a global framework to govern the military use of Artificial Intelligence (AI) by proposing inclusive and humane ways to forge cooperation. Three novel humanist conceptions are introduced: common good governance, transnational networked cooperation, and humanity's security.
Keywords: Artificial Intelligence -- Military Applications -- Law and Legislation; Artificial Intelligence -- Military Applications -- Government Policy; International Cooperation; Warfare and Defense